Hyperimmune egg-based IgY-rich formulations as adjuvant therapy in a murine model of vaginal candidiasis - Mihai Mares; Andra Cristina Bostanaru Iliescu; Bogdan Minea; Robert Capota; Dana Ciausu Sliwa; Valentin Nastasa (Journal of Global Antimicrobial Resistance)
AIM: Evaluating the preventive efficacy and adjuvant role in therapy of two products containing immunoglobulin Y, ImunoinstantG and Imunoinstant Anti-Candida albicans, in a murine model of vaginal candidiasis. BACKGROUND: Vaginal infections caused by Candida albicans affect approximately 75% of women, with recurrence involving immune imbalances in 5-8% of cases. METHODS: Thirty female Balb/C mice were equally divided into three groups: Control (C), ImunoinstantG (IG), and Imunoinstant Anti-Candida albicans (IA). Over 22 days, each experimental group received a dose/kg equivalent to an adult human weighing 70 kg (0.9 mg IgY/mouse in 0.35 mL) administered via gavage. The control group received the same volume of drinking water. Both products were administered preventively, starting 7 days before infection. Infection was induced by intravaginally inoculation of 20 µL suspension of Candida albicans wild-type SC5314, containing 2 × 10⁵ CFU. The fungal load (CFU/mL) was assessed in vaginal lavage on days 5, 10, and 15 post-infection. RESULTS: At 15 days post-infection, the fungal load was 2.1 × 10⁴ CFU/mL in group C, 0.4 × 10³ CFU/mL in group IG, and 0.9 × 10² CFU/mL in group IA, respectively. The reduction rate of the fungal load was highest in group IA at all evaluation points, reaching 99.6%. Cytological examination of the lavage fluid indicated a reduced presence of filamentous forms of the yeast and less inflammation for both ImunoinstantG and Imunoinstant Anti-Candida albicans treatments. CONCLUSIONS: These products demonstrated real preventive and therapeutic qualities, based on the significant and gradual reduction in vaginal fungal load throughout the administration period.